Looking at the problem of cytomegalovirus and Epstein-Barr viral infection in gynecology and possible solutions - Л. С. Осипова; А. А. Суханова; Е. И. Соколова (Publishing House TRILIST, 2017)
In recent years, there has been an increase in the number of patients suffering from chronic recurrent herpes-viral infections, which in many cases are accompanied by a pronounced disturbance in overall well-being and a number of therapeutic complaints. In particular, on transplantology and gynecology often have diseases and syndromes caused by cytomegalovirus (type V herpes viruses) and Epstein-Barr virus (type IV herpes viruses). The article presents the results of the effectiveness and experience of using an antiviral drug with the immunomodulatory action of Groprinosin® (inosine pranobex) in the treatment of chronic persistent conditions caused by cytomegalovirus infection and infection of the Epstein-Barr virus. Patients with verified cytomegalovirus infection and Epstein-Barr virus infection were examined. Group I included 56 women with active cytomegalovirus infection; group II - 49 women with active Epstein-Barr virus infection. The control group consisted of 30 healthy women. All patients received in complex therapy Groprinosin® 50 mg per kg of body weight per day for 2 weeks, then 2 tablets (1000 mg) once a day, regardless of body weight for 2 weeks (3 such courses during the 3 months). The daily dose of Groprinosin® was divided into 3-4 doses. After 3 months, the cytomegalovirus DNA was detected in spittle of 3 (5.3%) patients of group I, Epstein-Barr virus DNA - in 2 (4.0%) patients of group II. After treatment in patients receiving complex therapy Grosprinosin®, the quantitative indices of T-lymphocyte subpopulations were restored and their imbalance was eliminated (the immunoregulatory index was normalized), the same dynamics was also observed with regard to the number of natural killers. Based on the conducted studies, it was found that the inclusion of Grosprinosin® in the complex therapy of cytomegalovirus infection and infection with the Epstein-Barr virus promotes an increase in the immunological reactivity of the organism, allowing to significantly improve the clinical course of the disease. Grosrinosin® is well tolerated by patients and can be recommended for the treatment of both of these infections.